Pemberdayaan Kelompok Peduli Hipertensi Untuk Pengendalian Marker Sindrom Kardiometabolik Melalui Senam Rutin - Dwi Novitasari; Dwi Agus Yulianto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Every year, the old population in Central Java has a similar profile to the rise in the country. NCDs are frequently to blame for premature death before age 70. Globally, cardiovascular disease is the leading cause of death. According to a research of five participants, the average blood pressure was 125.4/80.9 mmHg, and the intermediate total cholesterol level was 168.9 mg/dl. Objective: Improve the health behavior of members of the hypertensive care group in the Eastern Purwokerto Mersi Kelurahan, especially by exercising intensively and consistently. Methods: Making pamphlets, providing tools and materials for cholesterol testing, and coordinating with the head of the hypertension care group are all part of this community service technique. At the end of the Public Health Service (PHS), the number of participants was 48. Results: Most PHS participants are women, 44 (91.7 %). 21 (43.7 %) have overweight to level 2 obesity. Seven (14.6 %) of the participants have previously had DM. Twenty-nine (60.4 %) suffer from hypertension. Of most PHS participants, 27 (56.3%) had a history of hypercholesterolemia, 36 (75.0%). There was an improvement in pre-normal cholesterol levels of practitioners by 36 (75.0%) to 28 (58.3%). Conclusion: This PHS activity has good active participation of the hypertension care group Mersi, Purwokerto members. There's been an improvement in the exercise participants' cholesterol levels.